2014
DOI: 10.1002/pamm.201410492
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of damage in cold bulk forming processes

Abstract: In the present paper a practically relevant extension of the known modelling methods with regard to the description of forming limits of steels typically used in the cold bulk forming is developed and implemented in a commercial finite element code Abaqus. The modeling approach is based on the so-called micromechanical damage concepts which represent the microstructure evolution more detailed than phenomenological models and, therefore, provide better prediction of damage and failure during the forming process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This also applies to the types of initial damage. As published by Rice et al, the stress-assisted plastic deformation promotes the nucleation and growth of micro-voids ( [33], Figures 7,8 and 10), whereby the shown central role of the non-metallic MnS-inclusions (Table 2 and Figures 7 and 10) is also indicated by Zapara/Augenstein/Helm [34]. The MnS-inclusions are known to induce anisotropic material behavior [35] including the behavior under cyclic load sequences ( [36], for forged and hardened medium carbon steel [37]).…”
Section: Discussionmentioning
confidence: 54%
“…This also applies to the types of initial damage. As published by Rice et al, the stress-assisted plastic deformation promotes the nucleation and growth of micro-voids ( [33], Figures 7,8 and 10), whereby the shown central role of the non-metallic MnS-inclusions (Table 2 and Figures 7 and 10) is also indicated by Zapara/Augenstein/Helm [34]. The MnS-inclusions are known to induce anisotropic material behavior [35] including the behavior under cyclic load sequences ( [36], for forged and hardened medium carbon steel [37]).…”
Section: Discussionmentioning
confidence: 54%
“…Forming-induced ductile damage occurs in the form of pores in the matrix material or at non-metallic inclusions, leading to local stress increases [ 11 , 12 ]. The resulting material or component failure under service conditions can be attributed to inhomogeneities [ 13 ], which have been addressed by various authors in their studies on the correlation between fatigue performance and defects, as the defects are determined by the threshold condition for small crack nuclei at the defect tip [ 14 , 15 ]. In addition, a correlation has been shown between the torsional fatigue limit and the threshold for non-propagating branched cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Hardness changes due to strain hardening, induced residual stresses due to inhomogeneities of the elastic and resilient properties of material matrix, different phases as well as non-metallic inclusions and general microstructural changes with respect to grain orientation and size changes have been investigated [1]. Furthermore, additional forming-induced damage should be considered, which is characterized as pore formation at non-metallic inclusions or different microstructural stress increases under applied forming load, which locally lead to stress increases [2]. In this context, Meya et al [3] found that radially superimposed stresses during forming reduced the number of voids, which had a positive effect on performance in terms of energy absorption during notched bar impact tests.…”
Section: Introductionmentioning
confidence: 99%